2009
DOI: 10.1111/j.1365-2133.2009.09208.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of sulfasalazine and pentoxifylline (low-cost antitumour necrosis factor drugs) as adjuvant therapy for the treatment of pemphigus vulgaris: a comparative study

Abstract: The use of PTX and SSZ as adjuvant therapy in the treatment of PV induced a faster and more significant decrease in the serum level of TNF-alpha, and this decrease was associated with rapid clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…This could be attributed to the synergistic effect of the two used immunosuppressive modalities; pulse steroid therapy and cyclophosphamide leading to the rapid dampening of the Th2 response and IL-4 production and thereby decreasing the IgG4 production. In addition, both drugs directly inhibit antibody production by B cells [11]. Furthermore, the use of two anti-tumor necrosis factor (TNF) a drugs; sulphasalazine and pentoxifylline down regulates the production and action of TNFa on TNF receptors 1 and 2, which has a crucial role in the production of blisters in PV [3,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the synergistic effect of the two used immunosuppressive modalities; pulse steroid therapy and cyclophosphamide leading to the rapid dampening of the Th2 response and IL-4 production and thereby decreasing the IgG4 production. In addition, both drugs directly inhibit antibody production by B cells [11]. Furthermore, the use of two anti-tumor necrosis factor (TNF) a drugs; sulphasalazine and pentoxifylline down regulates the production and action of TNFa on TNF receptors 1 and 2, which has a crucial role in the production of blisters in PV [3,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both drugs directly inhibit antibody production by B cells [11]. Furthermore, the use of two anti-tumor necrosis factor (TNF) a drugs; sulphasalazine and pentoxifylline down regulates the production and action of TNFa on TNF receptors 1 and 2, which has a crucial role in the production of blisters in PV [3,10,11]. However, the significantly better results observed in the group (B) patients who received IFN in combination with our standard therapy is a further proof to the boosting effects of IFN addition to the standard PV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the benefit of corticosteroid-sparing regimens four more controlled prospective clinical studies have been performed applying cyclophosphamide, cyclosporine, dapsone, and sulfasalazine plus pentoxifylline [26][27][28][29]. Only the combination of sulfasalazine and pentoxifylline was shown to be advantageous compared to the control group whereas in patients of the cyclosporine group, significantly more adverse events were seen [27,29].…”
Section: Pemphigusmentioning
confidence: 99%
“…Only the combination of sulfasalazine and pentoxifylline was shown to be advantageous compared to the control group whereas in patients of the cyclosporine group, significantly more adverse events were seen [27,29]. Very recently, the retrospective analysis of 136 pemphigus patients adjuvantly treated with methotrexate in 7 studies revealed a clinical improvement in more than 80% of patients [30].…”
Section: Pemphigusmentioning
confidence: 99%
“…These uniform parameters will then permit meta-ana lyses to be performed to compare studies, even if the numbers are relatively low, and provide better evidence for the treatments being assessed. New approaches to treatment are developing, such as the use of sulfasalazine and pentoxifylline [74].…”
Section: Five-year Viewmentioning
confidence: 99%